Combined role of green productivity growth, economic globalization, and eco-innovation in achieving ecological sustainability for OECD economies. (15th January 2022) - Ahmad, Munir; Wu, Yiyun
Abstract: Since climate change is the paramount concern of recent literature, macroeconomic factors such as green growth and economic globalization may play an integral role in achieving ecological sustainability in the presence of eco-innovation. However, the combined contributions of green growth, economic globalization, and eco-innovation towards achieving ecological sustainability are missing from the existing knowledge. Therefore, we investigate the combined influence of these variables in the presence of human capital, financial development, and gross domestic product on ecological footprint per capita for a panel of 20 Organization for Economic Co-operation and Development (OECD) countries from 1990 through 2017. The method of panel quantile regression is used to produce sound results across varying levels of the ecological footprint of OECD nations. The main results are as follows: firstly, green productivity growth linearly and non-linearly mitigates the ecological degradation, presenting a more pronounced ecological protection impact for higher quantiles, followed by medium and lower quantiles. Secondly, economic globalization manifests mixed effects: it induces ecological deterioration impact in the absence of its interaction with eco-innovation, while it brings about an ecological protection impact with the interaction term. Thirdly, eco-innovation demonstrates an ecological protection impact for all quantiles, with the most influential impact in countries with higher ecological footprint per capita, followed by medium and lower footprints. Based on empirical results, we propose productive utilization of environmental resources for ecological sustainability through product and process innovation and efficient management practices. Besides, we recommend cultivating energy-efficient and clean environmental technologies for long-term ecological sustainability. Highlights: Combined influence of green productivity growth, economic globalization, and eco-innovation. Panel quantile regression estimated heterogenous impacts across diversified ecological footprint. Green productivity growth and eco-innovation mitigate ecological degradation. Economic globalization without interactive term of eco-innovation depicts ecological degradation. Economic globalization interacting with eco-innovation portrays ecological protections.